Analysis of Design Indicators of Sustainable Buildings with an Emphasis on Efficiency of Energy Consumption (Energy Efficiency) - Damirchi Loo, Leila; Mahdavinejad, Mohammadjavad (Civil Engineering Journal, 2018)
Nowadays paying attention to sustainable development issues has been a priority for different countries, due to technological advances and increasing number of problems caused by neglecting the environment. Sustainable development is a new field that considers all the aspects of human life. One of important issues in this area is, considering the energy and efficient energy consumption and reducing the environmental consequences of its consumption. Sustainable design of buildings is also an example of sustainable development. The purpose of this study that has been conducted based on documents and library studies and analysis of samples that are built with the sustainable approach is to study and compare the fundamentals of investigated samples with the criteria of sustainable development. The result is that fundamentals of these buildings as architectural responses can help architectures challenges in different environmental conditions.